1986
DOI: 10.1007/bf01404485
|View full text |Cite
|
Sign up to set email alerts
|

MDCK cysts: An in vitro model of epithelial cyst formation and growth

Abstract: SUMMARY: MDCK cells dissociated from monolayer culture were either dispersed within medium-hydrated collagen gel or seeded atop a collagen substrate which was immediately overlaid with collagen gel. Individual cells exhibited clonal growth in three dimensions to form spherical cysts in which a simple epithelium surrounded a fluid-filled lumen. The ceils of MDCK cysts were polarized with apical surface bordering the lumen. MDCK cysts increased in diameter with continued culture. Maximum cyst size was dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…For 3D MDCK culture, 40 cells were trypsinized and resuspended to 3 × 10 4 cells/ml in a type I collagen solution containing PureCol (3 mg/mL), Advanced BioMatrix 5005-B, 10× MEM, NaHCO 3 (2.35 mg/mL), l -glutamine (29.2 mg/mL), and 1 M HEPES (pH 7.6). Cells in suspension were added to wells containing a cell-free collagen mix (polymerized previously at 37 °C) and were incubated at 37 °C (without CO2) for 20–30 min.…”
Section: Methodsmentioning
confidence: 99%
“…For 3D MDCK culture, 40 cells were trypsinized and resuspended to 3 × 10 4 cells/ml in a type I collagen solution containing PureCol (3 mg/mL), Advanced BioMatrix 5005-B, 10× MEM, NaHCO 3 (2.35 mg/mL), l -glutamine (29.2 mg/mL), and 1 M HEPES (pH 7.6). Cells in suspension were added to wells containing a cell-free collagen mix (polymerized previously at 37 °C) and were incubated at 37 °C (without CO2) for 20–30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Bissell, Mostov, and others have pioneered the use of 3D collagen and laminin (i.e., Matrigel) gels in organotypic cultures that recreate the epithelial morphogenetic developmental program ( O’Brien et al, 2002 ; Mroue and Bissell, 2013 ). In these natural matrices, epithelial cells, such as MDCK cells, proliferate from single cells to form multicellular, hollow spherical monolayer structures (cysts) within 10 d that bear the hallmarks of epithelial polarity, recapitulating the morphogenetic program for the formation of a rudimentary epithelial organ ( McAteer et al, 1986 ). These 3D cultures have revealed that interactions between integrin adhesion receptors and secreted laminin and the density of ECM, which impacts the gel mechanical properties, regulate the establishment of cell polarity and morphogenesis as well as tumorigenesis ( Barcellos-Hoff et al, 1989 ; O’Brien et al, 2001 ; Wozniak et al, 2003 ; Levental et al, 2009 ; Provenzano et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using 3D collagen and laminin gel cultures have demonstrated that the epithelial morphogenesis developmental program is regulated by biochemical and mechanical signals that result from cell-BM interactions (O'Brien et al, 2002; Yu et al, 2005; Mroue and Bissell, 2013). In these studies, single-cell encapsulation of epithelial cells, such as MDCK cells, results in cell proliferation into a multicellular aggregate and further development of cysts composed of a polarized epithelial monolayer that recreates the morphogenesis of epithelial organs (McAteer et al, 1986). Although these natural matrices have been able to recapitulate the epithelial morphogenesis program of MDCK cells, they do not offer the capacity to study individual contributions of the mechanical and biochemical properties of the ECM towards epithelial morphogenesis.…”
Section: Applications Of Bm-mimicking Hydrogelsmentioning
confidence: 99%